Enhanced photothermal conversion performances with ultra‐broad plasmon absorption of Au in Au/Sm2O3 composites. Issue 8 (29th April 2020) - Yu, Yang; Xu, Sai; Gao, Yuefeng; Jiang, Muhan; Li, Xiangping; Zhang, Jinsu; Zhang, Xizhen; Chen, Baojiu
Abstract: Lanthanide oxides are ideal candidates as photothermal conversion agents owing to their larger photon energy and advantages in biomedical applications. However, the small absorption cross section of rare earth is not conducive of absorbing near infrared light, which will affect the photothermal conversion efficiency of lanthanide oxides. Herein, Au particles are successfully introduced into Sm2 O3 to form Au/Sm2 O3 composites. The investigation of broadband emission and thermal performances in Sm2 O3 and Au/Sm2 O3 composites confirm the ultra‐broad plasmon absorption of Au induced thermal effect is in favor of the formation of broadband emission, meanwhile, enhances the photothermal conversion capability of Au/Sm2 O3 composites. The temperature increases of the Au/Sm2 O3 composites are 5.5°C and 19.6°C compared to Sm2 O3 particles under the irradiation of near infrared laser with power density of 11.5 and 29.0 mW/mm 2, respectively. In additional, the enhanced photothermal conversion effect is confirmed by the alcohol volatilization experiment and visual infrared thermal images. We present here an idea for enhancing the photothermal conversion capabilities of lanthanide oxides and highlight the promise of using this kind of materials for photothermal therapy.